Seed Quality and Yield as Influenced by Bio-Formulation in Garden Pea (Pisum sativum L.) - Sarma, C.; Bora, G C; Deka, S. D.; Goswami, P. K. (Current Research Progress in Agricultural Sciences Vol. 5, 2024)
Pea (Pisum sativum L.), one of the most popular annual legume crops of India, belongs to the family Leguminosae (Fabaceae) and sub-family Papilionoideae. It is a protein-rich, self-pollinated, cool-season vegetable crop grown throughout the world. Research work was conducted at Assam Agricultural University, Jorhat during the rabi season of 2021-2022 to investigate the influence of bio-formulation on seed quality and yield in garden peas. The Laboratory experiment was conducted following Completely Randomized Design for germination and seed vigour characteristics whereas a field experiment was laid out in factorial Randomized Block Design replicated three times for assessing plant growth and yield attributing characters. The experimental material comprised two varieties of garden pea viz., Arkel and DS-10 and seven treatments such asT1- Control, T2- Hydropriming, T3- seed priming with Trichoderma viride @ 5g/kg, T4- PSB @ 10g/kg, T5- Rhizobium @ 20 g/kg, T6- PSB @ 10g/kg + Rhizobium @ 20 g/kg and T7- Pseudomonas fluorescens @ 10 g/kg. Before sowing, seeds of both varieties were soaked in water for 4 hours and bio-primed with the above-mentioned bio-formulations. Results revealed significant differences amongst the treatments for most of the plant growth-promoting and yield-attributing characters. Among all the treatments, T6 i.e. seed priming with combined application of Rhizobium @ 20 g/kg + PSB @ 10g/kg exhibited the highest performance for most of the characters evaluated under laboratory and field conditions. Regarding the variety, DS-10 performed better as compared to Arkel. The experiment revealed that priming treatments had significantly enhanced the germination, seed vigour and yield attributing characters. From the present study, it could be concluded that seed priming with combined application of PSB + Rhizobium for 4 hours exhibited better performance in seed quality, yield and its attributing characters as compared to other treatments under field and laboratory conditions. From this investigation, combined application of PSB @10g/kg + Rhizobium @ 20g/kg may be promoted for future recommendation as a seed priming treatment in peas. Therefore, it may be suggested to treat the seeds with bio-formulation for better seed production and seed yield in garden peas.